Factors Associated With Long-term Survival in Women Who Get Pregnant After Surgery for WHO Grade II Glioma. (5th July 2022) - Ng, Sam; Duffau, Hugues
Abstract : Background and Objectives: Women with a World Health Organization grade II glioma (GIIG) often question clinicians about the effects of pregnancy on their disease. Previous reports have indicated a higher risk of glioma progression during and after pregnancy. Here, the aim was to investigate postpregnancy outcomes and predictive factors affecting overall survival in female patients who underwent GIIG surgery. Methods: Inclusion criteria were adult women who have been pregnant after a GIIG resection and with a stable oncologic status at the time of pregnancy (no ongoing oncologic treatment, no contrast enhancement, no debilitating clinical condition). Relevant cases were identified from a databank (1998–2021) of patients who underwent surgical resection for a histologically confirmed GIIG in our department. Results: Among 345 women with GIIG in their reproductive years (age <45 years), 16 patients (4.6%, mean age at delivery 30.9 ± 5.1 years) were pregnant (twice in 5 cases). The mean interval between the last oncologic treatment (surgery alone in 11 patients, surgery followed by chemotherapy and/or radiotherapy in 5 patients) and pregnancy was 3.5 years (range 0.75–10 years). Two patients experienced seizures during pregnancy. The delivery was vaginal and uneventful in all cases but 1 (1 caesarean). All children had normal mental and physical development. The glioma behavior changed in 7 patients (43.7%), with an acceleration of the velocity of diameter expansion and/or the occurrence of a contrast enhancement during or within 3 months after pregnancy, resulting in medical treatment and/or reoperation in the early postpartum period in 7 cases. The median clinical follow-up from delivery was 5.3 years (range 1.25–11.6 years). Four other patients received delayed adjuvant therapy for glioma progression. Seven patients (43.7%) died at a median time from delivery of 3.9 years (range 1.25–5.9 years). Overall, the median survival from delivery was 5.75 years. A crucial finding is that patients who underwent a complete surgical resection and patients with stable lesions before pregnancy lived longer (log rank, p = 0.046 and p = 0.0026, respectively). Discussion: Tumor residual volume and tumor speed growth are strong predictive factors conditioning postpregnancy long-term survival in patients with GIIG. Identifying patients at risk is critical to provide relevant counsel to women with GIIG with a desire for motherhood.